2002
DOI: 10.1034/j.1600-0749.2002.02007.x
|View full text |Cite
|
Sign up to set email alerts
|

The Etiology of Oculocutaneous Albinism (OCA) Type II: The Pink Protein Modulates the Processing and Transport of Tyrosinase

Abstract: Oculocutaneous albinism (OCA) is caused by reduced or deficient melanin pigmentation in the skin, hair, and eyes. OCA has different phenotypes resulting from mutations in distinct pigmentation genes involved in melanogenesis. OCA type 2 (OCA2), the most common form of OCA, is an autosomal recessive disorder caused by mutations in the P gene, the function(s) of which is controversial. In order to elucidate the mechanism(s) involved in OCA2, our group used several antibodies specific for various melanosomal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 43 publications
4
68
0
Order By: Relevance
“…It has been proposed to regulate melanosomal pH, 15 with an additional possible role in the processing and trafficking of melanosomal proteins. 17,18 It has recently been confirmed as localizing with mature melanosomes. 19 There have been numerous mutations and polymorphisms found in the OCA2 locus, which are listed on the International Albinism Center Database (http://albinismdb.med.umn.edu).…”
Section: Introductionmentioning
confidence: 91%
“…It has been proposed to regulate melanosomal pH, 15 with an additional possible role in the processing and trafficking of melanosomal proteins. 17,18 It has recently been confirmed as localizing with mature melanosomes. 19 There have been numerous mutations and polymorphisms found in the OCA2 locus, which are listed on the International Albinism Center Database (http://albinismdb.med.umn.edu).…”
Section: Introductionmentioning
confidence: 91%
“…Alterations in substrate levels could in turn have downstream effects on ion transport between the cytosol and other compartments, such as the ER. Such effects might alter folding or disulfide bond formation of proteins such as tyrosinase in the ER, perhaps explaining the reduced rate of processing and ER exit of tyrosinase in OCA2-deficient melanocytes (Toyofuku et al, 2002). Tyrosinase contains 15 lumenal Cys residues and many intramolecular disulfide bonds (Wang and Hebert, 2006), so changes in the disulfide bonding capacity of the ER could have a significant effect on tyrosinase maturation.…”
Section: Discussionmentioning
confidence: 99%
“…OCA2-immunoreactive subcellular fractions from melanocytes contain ER markers as well as melanin, and OCA2 colocalized extensively with ER markers by indirect IFM (Chen et al, 2002). Moreover, cells that lack OCA2 show a reduction in terminal glycosylation of Tyr (Chen et al, 2002;Toyofuku et al, 2002), suggesting that OCA2 activity might provide an optimal environment within the ER to facilitate Tyr folding. Thus far, this controversy has not been resolved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The P protein is a membrane protein with similarity to the Escherichia coli Na ϩ /H ϩ anti-porter protein. The exact function of the P protein is enigmatic, and the idea that it regulates melanosomal pH is inconsistent with the results of Toyofuku et al (2002) and Chen et al (2002), who showed that P protein is involved in processing and sorting of tyrosinase, which is retained in the endoplasmic reticulum in mutant melanocytes. It is also inconsistent with the observation of Staleva et al (2002), who showed that the P protein may be involved in glutathione metabolism.…”
Section: Melanosome Functionmentioning
confidence: 93%